2015
DOI: 10.1093/gerona/glu244
|View full text |Cite
|
Sign up to set email alerts
|

Aging Exacerbates Pressure-Induced Mitochondrial Oxidative Stress in Mouse Cerebral Arteries: Figure 1.

Abstract: Epidemiological studies demonstrate that in addition to the increased prevalence of hypertension in old patients, the deleterious cerebrovascular effects of hypertension (including atherosclerosis, stroke, and vascular cognitive impairment) are also exacerbated in elderly individuals. The cellular mechanisms by which aging and hypertension interact to promote cerebrovascular pathologies are not well understood. To test the hypothesis that aging exacerbates high pressure-induced mitochondrial oxidative stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 43 publications
3
59
0
Order By: Relevance
“…Results of previous experimental studies by our laboratories (Toth et al ., 2015b), and by others (Wakisaka et al ., 2010a,b), identify oxidative stress as a critical factor contributing to hypertension‐induced MMP activation and pathogenesis of CMHs and demonstrate that high intraluminal pressure per se (via increased wall tension‐dependent cellular stretch) is a key stimulus for increased vascular production of ROS (Ungvari et al ., 2003; Springo et al ., 2015; Toth et al ., 2015b) that lead to MMP activation. To elucidate the likely mechanism contributing to the exacerbation of hypertension‐induced MMP activation in IGF‐1 deficiency, we compared pressure‐induced production of O2· in cerebral arteries isolated from IGF‐1‐deficient mice and their respective age‐matched controls using the redox‐sensitive dye dihydroethidium (DHE).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of previous experimental studies by our laboratories (Toth et al ., 2015b), and by others (Wakisaka et al ., 2010a,b), identify oxidative stress as a critical factor contributing to hypertension‐induced MMP activation and pathogenesis of CMHs and demonstrate that high intraluminal pressure per se (via increased wall tension‐dependent cellular stretch) is a key stimulus for increased vascular production of ROS (Ungvari et al ., 2003; Springo et al ., 2015; Toth et al ., 2015b) that lead to MMP activation. To elucidate the likely mechanism contributing to the exacerbation of hypertension‐induced MMP activation in IGF‐1 deficiency, we compared pressure‐induced production of O2· in cerebral arteries isolated from IGF‐1‐deficient mice and their respective age‐matched controls using the redox‐sensitive dye dihydroethidium (DHE).…”
Section: Resultsmentioning
confidence: 99%
“…This concept is supported by recent findings showing that age‐related exacerbation of hypertension‐induced MMP activation can be abolished by antioxidative treatments (Toth et al ., 2015b). Increased hypertension‐induced oxidative stress in aged arteries has been attributed to upregulation of NOX oxidases, increased mitochondrial ROS generation, and impaired Nrf2‐dependent antioxidant defense mechanisms (Ungvari et al ., 2011a,b; Springo et al ., 2015; Toth et al ., 2015b). There is evidence that inhibition of ROS synthesis by these sources can prevent development of CMHs in aging (Toth et al ., 2015b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Pung et al have shown that chronic inhibition of Complex I by rotenone blocks ischemia induced collateral artery growth in the coronary circulation via activation of adenosine monophosphate-activated kinase and the subsequent inhibition of mechanistic target of rapamycin (mTOR) and p70 ribosomal S6 kinase (126). Higher levels of cellular ROS, such as occurs during injury and disease, can lead to cell death via both mitochondrial-and nonmitochondrial-mediated pathways, especially in metabolically compromised conditions (6,23,29,38,93,138).…”
Section: Mitochondrial Energetics and Reactive Oxygen Species Productionmentioning
confidence: 99%
“…Although production of ROS by mitochondria appears to be an independent process under most conditions, recent reports indicate that ROS production by mitochondria can promote ROS production by the extramitochondrial NADPH oxidase system, or vice versa, via a positive feedback system (23,31,37,134,138). Thus, the interaction between the mitochondria and the cytosolic NADPH oxidase axis leads to cellular damage due to excessive production of ROS by a "ROS induced ROS" mechanism.…”
Section: Mitochondrial Energetics and Reactive Oxygen Species Productionmentioning
confidence: 99%